Design, modification and test of the conduction cooled high-current current leads for the superconducting magnet. (September 2017) - Peng, Quanling; Cheng, Da; Xu, Fengyu; Yang, Xiangchen; Wang, Ting; Wei, Xiaotao
Highlights: Conduction cooled current leads are used in a 2.1 K, 31 mbar cryogenic system. Comsol multiphysics are used for temperature profiles and heat load simulation. Impregnated epoxy improved the heat conductivity, increase mass density. A horizontal cryogenic test stand verifies the simulation results. Abstract: Conduction cooled current leads, which bring the current from the room temperature terminal down to the cryogenic environment, were used in common recently in large scale superconducting accelerators for its low cost, sample design and low heat load. In practice, the current lead is designed contained in a stainless steel tube. The heat load can be incepted in steps by thermal anchors, where one end is attached to the stainless steel tube, while the other end is connected with the cold shield of the cryomodule. Since the limitation of the welding technique, a thicker stainless steel tube needs to be used, and hence the thermal anchors cannot provide enough pressure to deform the tube enough to be in direct contact with the current lead, which may lead to temperature instability and bring extra heat load to the cryogenic system. An excellent option of epoxy filled current lead can realize the fully contact and reduce the heat load effectively. This paper will present the process of the current lead design, optimization, numerical simulation and cryogenic test, the test results show that the current lead can keep in a stable operation and low heat load.